Restoration of renal hemodynamics and functions during black cumin (Nigella sativa) administration in streptozotocin-induced diabetic rats - Yusuksawad M; Chaiyabutr N (Dove Medical Press, 2011)
Mariem Yusuksawad1, Narongsak Chaiyabutr21Department of Physiology, Faculty of Medicine, 2Department of Physiology, Faculty of Veterinary Science, Chulalongkorn University, Bangkok, ThailandBackground: Black cumin (Nigella sativa) is an ancient herbal medicine recommended by the World Health Organization. The antioxidant and antihyperglycemic effects of black cumin are well established. Amelioration of renal dysfunction in nephrotoxic rats with black cumin treatment has also been noted. However, the effect of black cumin treatment on renal dysfunction in diabetes mellitus has not been clarified. In this study, the effect of black cumin oil (BC) on changes in renal dysfunction and renal hemodynamics in streptozotocin-induced diabetic rats was evaluated.Methods: The experiments were performed in male Sprague Dawley rats, divided into four groups (seven in each group): (1) normal rats given tap water (CON); (2) normal rats administered with BC (CON-BC); (3) diabetic rats given tap water only (STZ); and (4) diabetic rats administered with BC (STZ-BC). Diabetes mellitus was induced in the rats by an injection of streptozotocin. BC was given orally at the dose of 1000 mg/kg body weight to the rat in either CON-BC or STZ-BC every day for 8 weeks. Renal hemodynamics and functions in each rat were studied.Results: Renal hemodynamic changes in STZ-BC rats appeared to increase in terms of glomerular filtration rate, effective renal plasma flow, and effective renal blood flow, while renal vascular resistance and filtration fraction were decreased in comparison with diabetic rats given tap water only (STZ). An improvement of renal tubular dysfunction in STZ-BC rats was indicated by the decreases in fractional excretion of water and Mg++.Conclusion: An administration of BC can restore changes in renal hemodynamics and renal dysfunction in streptozotocin-induced diabetic rats.Keywords: black cumin, Nigella sativa, renal hemodynamics, renal dysfunction, fractional excretion of Mg++, streptozotocin-induced diabetic rats